The Myth of Bill Guppy: A Commentary - Sedlock, David (Ontario History)

(untitled) (The Ontario Historical Society, 2024)
Much of what we know about Archibald Belaney (aka Grey Owl) between his arrival in Halifax in April 1906 and his appearance in Temagami in the spring of 1907, is derived from a story told by Bill Guppy through author Hal Pink in 1940. This commentary analyses the story in light of well-established historical facts and internal coherence, and concludes that it cannot bear the weight that later historians have placed on it.